Benefit morale and cross-country diversity in sick pay entitlements - Daniel Arnold (University of Trier, Institute for Labour Law and Industrial Relations in the European Union (IAAEU), 2012)
This paper analyzes the impact of a country's level of benefit morale on generosity of sick pay entitlements by means of a political economy model and an empirical investigation. Higher benefit morale reduces the incidence of absence. On the one hand, this makes insurance cheaper with the usual demand side reaction. On the other hand, being absent less often, the voter prefers less insurance. The former effect dominates at lower, the latter at higher levels of benefit morale. We present empirical evidence for both effects in a sample of 31 countries between 1981 and 2010.
Keywords: H53; P16; Z13; 330; sick pay insurance; political economy; work absence; social norms